Effects of methamphetamine on prenatally exposed children in Cape Town: cognition and intrinsic functional brain connectivity - Kwiatkowski, Maja Anna (Department of Psychology, 2015)
Methamphetamine use among pregnant women is an increasing problem in South Africa. The aim of this cross-sectional exploratory study was to examine the possible neurotoxic effects of prenatal methamphetamine exposure (PME) on cognition and the developing brain in a sample of affected children in Cape Town, South Africa. Thus, this is a two-part study: the first part examines the effects of PME on neuropsychological outcomes, and the second part examines the effects of PME on intrinsic functional brain connectivity. Children with PME (n = 23) and unexposed controls (n = 22) completed a battery of neurocognitive assessments, and a smaller sub-sample (n = 36; 19 children with PME, 17 unexposed controls) also underwent resting-state functional magnetic resonance imaging (RS-fMRI). Independent samples t-tests revealed that children with PME scored significantly more poorly on measures of IQ, learning and memory, confrontation naming, visual-motor integration, and fine motor co-ordination, when compared to controls. Hierarchical regression analyses confirmed that PME has a significant effect on cognitive performance, and that this effect largely withstands the effects of potentially confounding sociodemographic and anthropometric variables. Independent component analyses revealed significant betweengroup differences in functional brain networks detected in task-free RS-fMRI in children with PME. Specifically, there is evidence for compromised connectivity within and between the basal ganglia network and default mode network in children with PME. Overall, the findings contribute to the small but growing literature on the cognitive effects of PME. The current study is the first to document preliminary evidence indicating aberrant intrinsic functional brain connectivity in children with PME, and suggests that further investigation of potential associations between particular neurocognitive deficits and such aberrant connectivity might be warranted.